How business environment of countries along the Belt and Road impacts China’s OFDI efficiency: a stochastic frontier gravity model approach - Qi Gao; Qiang Wang; Wei Zhang (Humanities & Social Sciences Communications, 2024)
Abstract The Belt and Road Initiative (BRI) provides a new opportunity for the continued deepening of economic and trade cooperation between China and countries along the BRI route. However, different business environments among countries have led to the problem of a low and uneven distribution of China’s overall trade and investment efficiency in the countries along the route. Using the stochastic frontier gravity model, this study evaluates the efficiency of China’s outward foreign direct investment (OFDI) based on the data of 47 countries along the Belt and Road route from 2013 to 2019. The empirical results indicate that the efficiency level of China’s OFDI in countries located along the Belt and Road route is 43.39%, which suggests a regional imbalance. In terms of business environment factors, regulatory governance, civic discourse, government accountability, and regulatory quality in host countries have a positive impact on China’s OFDI. The positive effects of the BRI have enabled Chinese enterprises to better face factors such as political instability, corruption and imperfections in the legal system when investing abroad. The findings and suggestions could help the governments and enterprises of the countries along the route improve the business environment in a more targeted manner, enhance the space for economic and trade cooperation, and promote the common development of the countries along the route.